Synthesising the Relationships Between Food Web Structure and Robustness - Aislyn A. Keyes; Allison K. Barner; Laura E. Dee (Ecology Letters, 2024)
For many decades, ecologists have sought to understand the extent to which species losses lead to secondary extinctions—that is, the additional loss of species that occurs when resources or key interactions are lost (i.e. robustness). In particular, ecologists aim to identify generalisable rules that explain which types of food webs are more or less robust to secondary extinctions. Food web structure, or the patterns formed by species and their interactions, has been extensively studied as a potential factor that influences robustness to species loss. We systematically reviewed 28 studies to identify the relationships between food web structure and robustness to species loss and how the conclusions depend on methodological differences. Contrary to popular belief and theory, we found relatively consistent, positive relationships between connectance and robustness, among other generalities. Yet, we also found that conflicting conclusions about structure‐robustness relationships can be, in part, attributed to differences in the type of data that studies use, particularly studies that use empirical data versus those generated from theoretical models. This review points towards a need to standardise methodology to answer the open question of whether robustness and its relationship with food web structure and to provide applicable insights for managing complex systems.

Quantifying co‐extinctions and ecosystem service vulnerability in coastal ecosystems experiencing climate warming - Lexi N. Wilkes; Allison K. Barner; Aislyn A. Keyes; Dana Morton; Jarrett E. K. Byrnes; Laura E. Dee (Global Change Biology, 2024)
Climate change is negatively impacting ecosystems and their contributions to human well‐being, known as ecosystem services. Previous research has mainly focused on the direct effects of climate change on species and ecosystem services, leaving a gap in understanding the indirect impacts resulting from changes in species interactions within complex ecosystems. This knowledge gap is significant because the loss of a species in a food web can lead to additional species losses or “co‐extinctions,” particularly when the species most impacted by climate change are also the species that play critical roles in food web persistence or provide ecosystem services. Here, we present a framework to investigate the relationships among species vulnerability to climate change, their roles within the food web, their contributions to ecosystem services, and the overall persistence of these systems and services in the face of climate‐induced species losses. To do this, we assess the robustness of food webs and their associated ecosystem services to climate‐driven species extinctions in eight empirical rocky intertidal food webs. Across food webs, we find that highly connected species are not the most vulnerable to climate change. However, we find species that directly provide ecosystem services are more vulnerable to climate change and more connected than species that do not directly provide services, which results in ecosystem service provision collapsing before food webs. Overall, we find that food webs are more robust to climate change than the ecosystem services they provide and show that combining species roles in food webs and services with their vulnerability to climate change offer predictions about the impacts of co‐extinctions for future food web and ecosystem service persistence. However, these conclusions are limited by data availability and quality, underscoring the need for more comprehensive data collection on linking species roles in interaction networks and their vulnerabilities to climate change.

Quantifying the relative importance of variation in predation and the environment for species coexistence - Lauren G. Shoemaker; Allison K. Barner; Leonora S. Bittleston; Ashley I. Teufel (Ecology Letters, 2020)
Coexistence and food web theory are two cornerstones of the long‐standing effort to understand how species coexist. Although competition and predation are known to act simultaneously in communities, theory and empirical study of these processes continue to be developed largely independently. Here, we integrate modern coexistence theory and food web theory to simultaneously quantify the relative importance of predation and environmental fluctuations for species coexistence. We first examine coexistence in a theoretical, multitrophic model, adding complexity to the food web using machine learning approaches. We then apply our framework to a stochastic model of the rocky intertidal food web, partitioning empirical coexistence dynamics. We find the main effects of both environmental fluctuations and variation in predator abundances contribute substantially to species coexistence. Unexpectedly, their interaction tends to destabilise coexistence, leading to new insights about the role of bottom‐up vs. top‐down forces in both theory and the rocky intertidal ecosystem.

Generality in multispecies responses to ocean acidification revealed through multiple hypothesis testing - Allison K. Barner; Francis Chan; Annaliese Hettinger; Sally D. Hacker; Kelsey Marshall; Bruce A. Menge (Global Change Biology, 2018)
Decades of research have demonstrated that many calcifying species are negatively affected by ocean acidification, a major anthropogenic threat in marine ecosystems. However, even closely related species may exhibit different responses to ocean acidification and less is known about the drivers that shape such variation in different species. Here, we examine the drivers of physiological performance under ocean acidification in a group of five species of turf‐forming coralline algae. Specifically, quantitating the relative weight of evidence for each of ten hypotheses, we show that variation in coralline calcification and photosynthesis was best explained by allometric traits. Across ocean acidification conditions, larger individuals (measured as noncalcified mass) had higher net calcification and photosynthesis rates. Importantly, our approach was able to not only identify the aspect of size that drove the performance of coralline algae, but also determined that responses to ocean acidification were not dependent on species identity, evolutionary relatedness, habitat, shape, or structural composition. In fact, we found that failure to test multiple, alternative hypotheses would underestimate the generality of physiological performances, leading to the conclusion that each species had different baseline performance under ocean acidification. Testing among alternative hypotheses is an essential step toward determining the generalizability of experiments across taxa and identifying common drivers of species responses to global change.

Fundamental contradictions among observational and experimental estimates of non‐trophic species interactions - Allison K. Barner; Kyle E. Coblentz; Sally D. Hacker; Bruce A. Menge (Ecology, 2018)
The difficulty of experimentally quantifying non‐trophic species interactions has long troubled ecologists. Increasingly, a new application of the classic “checkerboard distribution” approach is used to infer interactions by examining the pairwise frequency at which species are found to spatially co‐occur. However, the link between spatial associations, as estimated from observational co‐occurrence, and species interactions has not been tested. Here we used nine common statistical methods to estimate associations from surveys of rocky intertidal communities in the Northeast Pacific Ocean. We compared those inferred associations with a new data set of experimentally determined net and direct species interactions. Although association methods generated networks with aggregate structure similar to previously published interaction networks, each method detected a different set of species associations from the same data set. Moreover, although association methods generally performed better than a random model, associations rarely matched empirical net or direct species interactions, with high rates of false positives and true positives, and many false negatives. Our findings cast doubt on studies that equate species co‐occurrences to species interactions and highlight a persistent, unanswered question: how do we interpret spatial patterns in communities? We suggest future research directions to unify the observational and experimental study of species interactions, and discuss the need for community standards and best practices in association analysis.

Solutions for Recovering and Sustaining the Bounty of the Ocean: Combining Fishery Reforms, Rights-Based Fisheries Management, and Marine Reserves - Allison Barner; Jane Lubchenco; Christopher Costello; Steven Gaines; Amanda Leland; Brett Jenks; Steven Murawski; Eric Schwaab; Margaret Spring (Oceanography, 2015)